The Community is Participating in The Independent Neighborhood Program for Economic Improvement in Banjarbaru City - Anjani, Anjani; Purboningsih, Dewi; Tjhia, Adellya Novelyn; Herawati, Lilis; Qosid, Nas (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
Improving the community’s economy is an achievement and one of the government’s successful efforts in implementing development. Neighborhood associations have a role in enhancing the community’s economy, so the role of Neighborhood Associations is vital in regional development. Communities are empowered because community members work together to improve development through their participation. Therefore, the Banjarbaru City Government, through the independent neighborhood program, provides space for the community to participate in economic empowerment. The policy is contained in the Banjarbaru City Regional Government’s Medium-Term Development Plan 2021-2026. One of the objectives of the Independent Neighborhood Program is to build micro, small, and medium enterprises at the neighborhood level to grow Banjarbaru’s micro, small, and medium enterprises. Funding assistance in the Independent Neighborhood program amounted to seventy-five million rupiah (Rp. 75,000,000) for each neighborhood association. This policy has been running since 2022 by providing business capital funding assistance to citizens of Banjarbaru City with a selection system for each sub-district to get a quota of three POKMAS (community groups). The research conducted used a qualitative approach. The research location was in Banjarbaru City. The data was collected through structured interviews, observations, and document studies published by the Banjarbaru City government. The conclusion is that the independent neighborhood program is one of the efforts of the Banjarbaru city government to mobilize and empower the community’s economy through development activities. The program’s goal is to improve the welfare of community groups and make the community more independent in their economy and able to contribute to development activities in their area. Community participation in this program is essential; most community groups are still at the implementation stage and can not be used for development activities. The program’s success is that all stakeholders actively participate in the independent neighborhood program